Active coping style and pharmacist's burnout during pandemic COVID-19: Core self-evaluation as a mediator - LailaMeiliyandrie Indah Wardani; Minak Cenggara Ramadhani Depati; Agnis Sombuling; Erna Risnawati (Universidad Tecnica de Manabi, 2022)
The aim of these study are to determine the effect of active coping style on pharmacist's burnout and whether the core self-evaluation as a personal resource has a role as a mediator between active coping style and pharmacist's burnout. The pharmacists work so hard to look for the antidote for the virus, so they have to work in shifts to meet the demand for medications, which sometimes cause them to experience burnout. Therefore, the pharmacist needs an active strategies and stable behaviors to deal and solve the problems, known as active coping style. Data were collected from 281 pharmaceutical industry using Core Self-Evaluation Scale by Judge, et. al., Simplified Coping Style Questionnaire by Xie, and Maslach Burnout Inventory-General Survey by Maslach. The data was analyzed using simple mediation regression model no. 4 PROCESS v4.0 by Hayes. The results show core self-evaluation is an effective mediator for the relationship between active coping styles and burnout. The result also indicated that self-esteem has the strongest relationship with and emotional exhaustion. This study highlight active coping style and core self-evaluation are essential for workers in the pharmaceutical industry to overcome their burnout.